How leadership styles and organizational beliefs affect Job satisfaction (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This study aims to model the effect on job satisfaction leadership style and organizationalbeliefs in a universe made up of 145 workers. To contrast the hypothesesa multiple regression equation was applied which results shown that the beliefs andleadership styles have an explanatory power of 31% on the general job satisfactionwhich is highly significant. Specifically the style culture of control beliefs has asignificantly negative influence on job satisfaction in general and the participativeleadership styles a positive and significant influence on job satisfaction in general.
Keywords: job satisfaction; leadership; organizational beliefs